P-158 Differences in Patient Expectations and Gastroenterology Practices in Osteoporosis Screening in Inflammatory Bowel Disease. (February 2017) - Chitnavis, Maithili; Ellis, Jim; Tuskey, Anne; Behm, Brian
Abstract : Background: Patients with inflammatory bowel disease (IBD) have a 40% higher risk of osteoporosis-associated fracture than the baseline population. AGA guidelines recommend that patients with prolonged corticosteroid use, hypogonadism, postmenopausal state in females, or age greater than 50 in males should be screened for osteoporosis; however, screening is often underutilized in this at-risk population. This study was developed to gauge IBD patients' knowledge and attitudes regarding osteoporosis risk, and to determine if these are congruent with provider practices. Methods: A one-page multiple choice patient survey and a 4-page practitioner survey were distributed from July 2015 to July 2016 at our institution. Patient surveys were distributed to patients during their appointment in the IBD subspecialty clinic; patients who did not carry a diagnosis of IBD were excluded. Practitioner surveys were distributed to attendees at regional gastroenterology conferences and to gastroenterology faculty at our institution. Surveys were approved by the institutional review board. Results: A total of 157 patient surveys were completed with a patient participation rate of 99.4%. The mean patient age was 42.7 years; the majority were female (58.6%) and had Crohn's disease (72.3%). Only 63.7% of patients stated that their providers had discussed their risk of osteoporosis with them, but 72.6% of patients were able to identify that IBD was a risk factor for development of osteoporosis. The majority of patients (60.5%) stated they had been screened for osteoporosis, but an additional 8.9% who had been screened answered that they had never had prior screening. The majority of patients felt their PCP should be solely responsible for screening for osteoporosis (47.8%); other patients felt that their GI provider should be responsible (20.4%) or that both GI and PCP should share responsibility (17.2%). Forty-nine respondents participated in the provider survey (11% response rate), of which 10 were excluded. The majority of respondents (56.4%) were physicians with an average of 16.4 years of experience following completion of training. Most providers (79%) were aware of the existence of guidelines regarding osteoporosis screening in IBD patients, and 79.5% of providers stated they screened their patients. The most important patient factors influencing their decision to screen were history of long-term steroid use, advanced age, and previous history of fragility fracture. The 2 most commonly cited reasons by providers for not addressing screening were that this was felt to be within the realm of the PCP's domain and not enough time to address screening during clinic visits. Conclusions: This study highlights attitudes regarding screening for osteoporosis in IBD patients. Approximately 9% of patients were unaware they had been screened for osteoporosis and only 63.7% recalled discussing osteoporosis risk with providers, which sheds light on the need for improving health literacy in this population. The majority of patients wanted PCP involvement in the decision to screen for osteoporosis, which could improve adherence with these measures. Osteopenia and osteoporosis have a high prevalence in this patient population; thus early identification and institution of therapy by bridging the gap between patient expectations and provider practices are crucial to achieve successful outcomes.